Effects of innovation types on firm performance: An empirical study on Pakistan's manufacturing sector - Masood ul Hassan; Sadia Shaukat; Muhammad Saqib Nawaz; Saman Naz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The main purpose of this study is to explore the effects of innovation types including product, process, marketing and organizational innovation on different aspects of firm performance such as innovative, production, marketing and financial performance in Pakistani manufacturing companies. Data were collected through survey questionnaires from 150 respondents mainly from production, R&D and marketing departments of manufacturing companies. With the help of SPSS, data were analyzed by factor, reliability, correlation, and regression analysis. The results reveal the positive effects of innovation types on firm performance. Theoretical and managerial implications along with limitations for future research have also been discussed.
Keywords: 330; Innovation types; firm performance; manufacturing sector; Pakistan